1986
DOI: 10.1002/j.1460-2075.1986.tb04348.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and structural characterization of a human non-erythroid band 3-like protein.

Abstract: Polypeptides which are immunologically related to the erythrocyte anion transport protein have been identified in a variety of non‐erythroid cells. We describe two cDNA clones encoding a human non‐erythroid band 3 protein (HKB3) and the mouse erythrocyte band 3 (MEB3) and show that these proteins are structurally similar. Comparison of the predicted amino acid sequences from HKB3 and MEB3 reveals a high degree of sequence homology (71%) and conservation of the overall topography of the transmembrane domain. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
1

Year Published

1987
1987
1998
1998

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(66 citation statements)
references
References 62 publications
(39 reference statements)
2
63
1
Order By: Relevance
“…The hydropathy plot of the chicken band 3 polypeptide reveals 10 very hydrophobic regions (A through J in Fig. 4) in the C-terminal portion of the molecule that are similar to those previously demonstrated for the murine erythroid (30) and human nonerythroid (15) polypeptide. Hydrophobic peaks A, C, E, and G (Fig.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The hydropathy plot of the chicken band 3 polypeptide reveals 10 very hydrophobic regions (A through J in Fig. 4) in the C-terminal portion of the molecule that are similar to those previously demonstrated for the murine erythroid (30) and human nonerythroid (15) polypeptide. Hydrophobic peaks A, C, E, and G (Fig.…”
Section: Resultssupporting
confidence: 78%
“…These studies revealed that the transmembrane domain of the chicken erythroid band 3 polypeptide is greater than 70% identical to the membrane-spanning region of the band 3 polypeptides from other species. The hydropathy profile suggests that chicken erythroid band 3 traverses the membrane 12 to 14 times, in agreement with previous results (15,30). Furthermore, many of the amino acids implicated in anion transport through drug binding studies are conserved in the chicken erythroid band 3 polypeptide.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Recently, the cDNA encoding a nonerythroid analogue of band 3 has been isolated and sequenced (Demuth et al, 1987). Although the overall degree of sequence identity in the cytoplasmic domain between the nonerythroid and erythroid band 3 was only 35 %, these workers identified a highly conserved region in this domain spanning residues 157-177, which they proposed to be the ankyrin-binding region (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Human AE1 protein has been purified and characterized (Lukakovic et al 1981), and its cDNA has been cloned and sequenced as well (Tanner et al 1988;Lux et al 1989). AE2 and AE3 transcripts (and corresponding cDNAs) were identified by cross hybridization with AE1 cDNA probes (Demuth et al 1986;Alper et al 1988;Kopito et al 1989;Kudrycki et al 1990;Lindsey et al 1990). The complete coding sequence of human kidney AE2 cDNA has also been described (Gehrig et al 1992).…”
Section: Introductionmentioning
confidence: 99%